2016
DOI: 10.1653/024.099.0336
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant Growth Regulators onBlissus insularis(Hemiptera: Blissidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
(7 reference statements)
2
7
0
Order By: Relevance
“…The combination of trinexpac-ethyl and ethephon resulted in intermediate reductions in 2017 and 2019 compared ethephon applications alone which would also support that trinexapac-ethyl either contains insecticidal properties, acts as a behavioral irritant or physiological antagonist against L. maculicollis larvae or activates plant defense pathways in P. annua (Krishnan & Merewitz, 2015). The two-fold reduction of L. maculicollis larvae in 2017 and 2019 studies are consistent with Kaur et al (2016) in which they observed reductions of chinch bugs populations in Stenotaphrum secundatum treated with trinexapac-ethyl. Although L. maculicollis adults and larvae are chewing pests, larval exposure to trinexapacethyl may be more similar to piercing-sucking insects where they acquire trinexapac-ethyl moving through the phloem.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The combination of trinexpac-ethyl and ethephon resulted in intermediate reductions in 2017 and 2019 compared ethephon applications alone which would also support that trinexapac-ethyl either contains insecticidal properties, acts as a behavioral irritant or physiological antagonist against L. maculicollis larvae or activates plant defense pathways in P. annua (Krishnan & Merewitz, 2015). The two-fold reduction of L. maculicollis larvae in 2017 and 2019 studies are consistent with Kaur et al (2016) in which they observed reductions of chinch bugs populations in Stenotaphrum secundatum treated with trinexapac-ethyl. Although L. maculicollis adults and larvae are chewing pests, larval exposure to trinexapacethyl may be more similar to piercing-sucking insects where they acquire trinexapac-ethyl moving through the phloem.…”
Section: Discussionsupporting
confidence: 72%
“…• L. maculicollis larvae rarely damage golf putting surfaces • We assessed nitrogen fertility and plant growth regulation effects on oviposition and survival • Females preferred moderate N levels as oviposition sites in lab assays • Fewer larvae were found in trinexapac-ethyl plots in two years, though higher in the third year • Nitrogen level had no effect on L. maculicollis larval densities in the field faster following exposure to paclobutrazol and trinexapacethyl compared to caterpillars that were not exposed (Rogers et al, 2001). Populations of chinch bugs (Blissus insularis Barber), insects that draw fluid from the plant through a piercing-sucking mouthpart, were reduced two-fold after trinexapac-ethyl application to Stenotaphrum secundatum (Walter) (Kaur et al, 2016). Stem-borers such as L. maculicollis, represent an intermediate feeding guild where the effect of PGRs is unclear.…”
Section: Core Ideasmentioning
confidence: 99%
“…One promising alternative may be the use of plant growth regulators (PGRs) against pest species. Several researchers have focused on the effects of various PGRs on herbivores, since these compounds may have considerable impacts on the survival, development and reproductive potential, as well as on other physiological processes and induction of the oxidative stress of many insect pests (Tsagkarakis etal., 2012;Prado and Frank, 2013;Abdellaoui et al, 2015;Kaur et al, 2016). Also, many authors (Kaur and Rup, 2002;Silva et al, 2003;Paulson et al, 2005;Abdellaouiet al, 2013) have even suggested the use of certain PGRs, like gibberellic acid (GA3) and Indole-3-acetic acid (IAA), as successful chemosterilants against insect pests.…”
Section: Introductionmentioning
confidence: 99%
“…The available literature contains many reported works focusing on the disruptive effects of PGRs on various insect pests leading directly to death or through impairment of their reproductive potential and other physiological processes Mu et al [16], Mendonça et al [17] and Kaur et al [18]. Also, many PGRs had been reported to deteriorate the food metabolism in different insects, through impairment of food ingestion, digestion, absorption and assimilation, such as Gibberellic acid against Bactrocera cucurbitae Kaur & Rup [9] Spodoptera littoralis Kaur & Rup [9] as well as JA against Spodoptera frugiperda Gordy et al [19].…”
Section: Introductionmentioning
confidence: 99%